Adolescent pregnancies: a 10-year single-center experience - Keskin, Deha Denizhan (The European Research Journal, 2020)
Objectives: To investigate adolescent pregnacy rate in last decade and emphasize the perinatal outcomes. Methods: Our study was a retrospective investigation of all women with singleton pregnancies who gave birth at > 20 weeks gestation aged 13-16 years old (early aged adolescent pregnancy group, n = 107), aged 17-19 years old (late aged adolescent pregnancy group, n = 991) and aged 20-35 years old (control group, n = 1,098) at Ordu University School of Medicine, Training and Research Hospital Obstetrics and Gynecology Clinic between January 2008 and January 2018. The variables used to determine the perinatal outcomes were low birth weight (birth weight < 2,500 g), macrosomic fetus (birth weight > 4,000 g) and stillbirth (delivery of infant > 20 weeks gestation without cardiac activity) prevalences were investigated and compared between groups. Results: Adolescent birth ratio to all births was 4.4% (1,098/24,560). Low birth weight rate was higher in the late aged adolescent group (p < 0.001). Cesarean section rate was significantly lower in the adolescent age group (40.2% in early aged and 7.2% in late aged)) whereas rate was 56.3 % in the control group. We attributed this to the high parity in the control group and the surplus of the old cesarean section indication (p < 0.001). Conclusions: Adolescent pregnancy, especially late aged adolescents were found to be closely related with low birth weight but there was no significant difference with respect to stillbirth rate in adult age group. Skilled antenatal, childbirth and postnatal care is very necessary to reduce low birth weight and therefore perinatal mortality.